Primary Productivity of the Cengklik Dam Boyolali - ARI PITOYO; WIRYANTO WIRYANTO (Society for Indonesian Biodiversity, 2002)
Primary productivity dynamic of the water ecosystem was conducted faster in the last decades. This study was intended to find out the primary productivity of Cengklik dam Boyolali, Central Java to explain the ecosystem dynamic and to lead the maintenance of dam. This study used quantitative methods in completely randomized group design (CRD), and the data was analized by Analysis of Variance (ANAVA). Samples were taken horizontally in four sampling point, respectively in the riparian zone, around of the floating net (â€œkarambaâ€), in the center of dam water and around of the ex-paddy fields. There were taken vertically in three-depth point in each of the sampling point, respectively 0.5 meter, 1.5 meter, and 2.5 meter. The results showed that the gross primary productivity of the dam was 11.122.500-22.545.600 mgC/m3/days, and the primary productivity differences in each of the point sampling caused by light intensity, nutrient supply, and abundance of the chlorophyll organisms.Â© 2002 Jurusan Biologi FMIPA UNS SurakartaKey words: primary productivity, Cengklik dam